Do the Integrated Health Posts Have Contextual Effect on Birth Weight? A Multilevel Evidence from Situbondo, East Java - Kuswandari, Eti; Salimo, Harsono; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2020)
Background: Low birth weight babies (LBW) are sensitive indicators of socioeconomic condi